An analysis of the correlation of clinical, endoscopic and histological classifications in Crohn’s disease - Durko, Łukasz; Stasikowska-Kanicka, Olga A.; Wagrowska-Danilewicz, Małgorzata; Danilewicz, Marian; Małecka-Panas, Ewa I. (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Introduction: The precise evaluation of Crohn’s disease (CD) activity is difficult mainly due to the complex symptoms of the disease. Establishing correlations between the most widely used scales of CD clinical, endoscopic and histopathological activity might help to identify the most accurate scale in the assessment of the course of CD. Aim: Comparison of the results of clinical, endoscopic and histological scales of CD activity, i.e. (Crohn’s Disease Activity Index (CDAI) score, Montreal Classification, Crohn’s Disease Endoscopic Index of Severity (CDEIS) and D’Haens classification). Material and methods: A group of 62 patients with CD was examined. All individuals underwent medical interview and physical examination. All patients had colonoscopy, at which the extent of the disease was analysed according to Montreal Classification and intensity of mucosal lesion described by CDEIS scale. Biopsy samples were taken during colonoscopy. Crohn’s disease activity was evaluated by clinical scales (Montreal Classification – A and B, CDAI), endoscopic scales (Montreal Classification – L, CDEIS) and histopathological classification by D’Haens. Results: The results of histopathological activity scale of CD by D’Haens correlated only with the results of endoscopic classification CDEIS. The results of CDEIS correlated also with parameter B of Montreal Classification. The analysis of Montreal Classification parameters showed correlations between the age of disease onset (A) and localization of the disease (L). Additionally, correlation of parameter A (age of onset) and B (behaviour of the disease) of Montreal Classification was observed. The values of clinical CDAI scale correlated only with parameter B of Montreal Classification (behaviour of the disease). Conclusions : There was a significant correlation between the histological (D’Haens) classification and endoscopic scale (CDEIS), but their results did not correlate with clinical scales. There was no consistent correlation between the clinical scales themselves however the correlations concerned only some parameters assessed, which may be the result of subjective clinicians evaluation of CD activity.